THE RELATIONSHIP OF KNOWLEDGE ON THE BEHAVIOR OF MOTHERS CARING FOR CHILDREN TODDLER WITH DIARRHEA - Arianusyanti, Riza; Utami, Tuti Asrianti (Universitas Respati Yogyakarta, 2020)
Diarrhea is an endemic illness in Indonesia and a potential case of Kasus Luar Biasa (KLB) is often accompanied by death. Easy diarrhea occurs in children, especially children toddlers. Respondents of the research were mothers of children toddler with diarrhea were treated in a private hospital child care in Lippo Village Tangerang in August-September 2017. The purpose of this study was to find out. the relationship of knowledge on the behavior of mothers caring for children toddler with diarrhea. The method used is a quantitative descriptive correlation with a cross-sectional study design. The technique of collecting data by distributing questionnaires. The data collection method by total sampling, the total sample of 53 respondents with the most respondents at the age of 31-40 years as many as 25 people (47.2%), Some of them are university graduated as many as 26 people (49,1%) most of them 32 people (60,4%) as a housewife, well educated as many as 41 people (77,4%) and well behaved as many as 45 people (84.9%). The results of this study indicate that there is no relationship between age (?-value = 0469), education (?-value = 0.075), job (?-value = 0632) with the behavior of mothers caring for children toddler with diarrhea and there is a relationship between knowledge and behavior of mother to toddler care for children with diarrhea (?-value = 0.045). Knowledge is the result out of someone on an object through its senses, so that a good mother knowledge about caring for children toddler with diarrhea, the mother will have good behavior, as well as his son, should be admitted to hospital because of diarrhea.